The role of entrepreneurship in economic development of the region - A. D. Petrova; V. M. Mineeva; G. H. Aznabaeva; E. R. Kalimullina (Путеводитель предпринимателя)
In the article the authors analyzed the entrepreneurial activities on the territory of the Republic of Bashkortostan, as well as the tendencies of development of small and medium businesses under favourable business climate. The methodology is the analysis of dynamics of development of business entities based on statistical data.